Factibilidad técnico-económica de un sistema de energía solar fotovoltaico “off grid” para suministro eléctrico residencial en el sector la Virginia de la ciudad de Quevedo - Muñoz Campoverde, Jean Alvaro (2022)
The present research proposes a technically and economically viable alternative that helps reduce the current energy shortage rate experienced by the residents of the "La Virginia" community situated in Quevedo city, with the purpose that the system complies with the total supply of the 12 homes that make up the sector. However, it will be a supply of clean energy and that fits the economic budget of those people, because their quality of life is not very favorable since they do not have an energy supply, and this is one of the basic needs at present of the human beings for their constant development. The location of the study area is favorable for capturing solar radiation that supports power generation.